A colorimetric and fluorescent dual-channel cyanide ion probe using crosslinked polymer microspheres functionalized with protonated Brooker's merocyanine. (May 2015) - Xiao, Kun; Nie, Hong-mei; Gong, Cheng-bin; Ou, Xiao-xiao; Tang, Qian; Chow, Cheuk-fai
Abstract: This paper describes the development of a colorimetric and fluorescent cyanide probe based on crosslinked polymer microspheres functionalized with a protonated merocyanine. The functionalised microspheres were prepared by free radical polymerization using 4-((E)-2-[(4-hydroxylphenyl) ethenyl-1-allyl pyridinium bromide as the functional monomer, ethylene glycol dimethacrylate as the crosslinker, and azobisisobutylnitrile as the radical initiator. Upon introducing CN – to a suspension of the functionalised microspheres in ethanol/H2 O (9:1, v/v), a change from yellow to red and a decrease in fluorescence intensity at 497 nm were immediately observed. This CN – probe can be reversed many times, which is cost efficient and beneficial to the environment. Analytical application of the functionlised microspheres to measure CN – concentration in spiked water samples was explored with good recoveries. Thus, the colorimetric and fluorescent CN − probe has high potential for the ultrasensitive detection of CN − in real samples. Graphical abstract: Highlights: Protonated Brooker's Merocyanine functionalised polymer microspheres was designed. The microspheres display colorimetric and fluorescent sensing properties toward CN – . The microspheres can be reversed for many times for monitoring and detection of CN – . The microspheres are applicable for determination of CN – in real samples.